Illness and grapes pests in the vineyard of Ukraine - Тарабрина, Ирина Викторовна (Eastern-European Journal of Enterprise Technologies, 2012)
General description of illnesses and wreckers of the sorts is given on the example of the table vine of Ukraine, the basic types of rots and bacterial cancer of the sorts are considered